Performance of grain sorghum hybrids resistant to acetolactate synthase and acetyl coenzyme‐A carboxylase inhibitor herbicides. Issue 2 (10th February 2021) - Weerasooriya, Dilooshi; Gobena, Dereje; Bandara, Ananda; Dowell, Floyd; Peiris, Kamaranga; Bean, Scott; Perumal, Ramasamy; Adee, Eric; Tesso, Tesfaye
Abstract: Acreage under grain sorghum [ Sorghum bicolor (L.) Moench] in the United States has sharply declined over the past several decades. Among the major causes are the lack of better postemergence weed control options. Farmers opt for crops and tools that allow better management of weeds, and sorghum is not one of them. The discovery of sources of resistance to acetolactate synthase (ALS) and acetyl‐coenzyme A carboxylase (ACCase) inhibitor herbicides in feral relatives of sorghum opened a new horizon for development of a resistance‐based weed control option for the crop. The objective of this study is to demonstrate the agronomic potential of sorghum hybrids resistant to ALS and ACCase inhibitor herbicides and shed light on concerns that deployment of resistance traits may cause yield drags. A total of 186 hybrids involving homozygous ALS resistant, homozygous ACCase resistant, heterozygous ALS and ACCase resistance, and conventional hybrids plus commercial checks were grown in three sets consisting of 68, 62 and 56 entries for Set I, Set II, and Set III, respectively. The experiments were conducted during the 2014 and 2015 season in three replications at Kansas State University Agronomy Research Farm near Manhattan, KS. Data were collected on plant height, maturity, yield, and yield components, as well as grain nutritional traits. The analysis of the data revealed that the resistance technology has no negative effect on agronomic adaptability, yield potential, and nutritional traits of grain sorghum.